Identity of a Muslim Family in Colonial Bengal Between Memories and History - Rashiduzzaman, Mohammad; Rashiduzzaman, Mohammad (Peter Lang, 2021)
Weaving personal remembrances with diverse sources including the author$1 (Bs academic research and field works, this book is an intriguing rural Muslim historiography in Colonial Bengal, a largely ignored swathe in South Asian history. The gripping true-life account is built around real people$1 (Bnot imagined characters. Between the twilight of the 19th century and nearly the first half of the 20th century, the Muslims in Colonial Bengal in India were haunted by their misgivings about an alien rule and its cohorts. The religiosity and identity questions, conflicting existential urges, the spiraling Hindu-Muslim discord, the feudal constraints, and marginalization by the bhadraloks swirled around them. Wracked by religious, cultural, social, and political conflicts, the old British Indian Bengal comes alive in this book$1 (Bs intergenerational narrative. With its 9 main chapters plus a preface and introduction, this volume seeks out average individuals$1 (Blife amidst such turmoil while it amplifies the larger challenges of the Muslims in undivided Bengal. Not rigidly structured, the multi-layered recount has utilized variable ways and means of research and innovative analysis. Authored by a well-published scholar on South Asia, this extraordinary study of a rural Muslim family in pre-partition Bengal addresses scholars, students, and specialists as well as the general readers. Framed by the known historical milieu and backed by reliable oral narratives, qualitative interviews, authentic memoirs, and scholarly sources, this is not a chronological memoir. Pertinent to the academics and refreshing to avid readers, this recount touches a range of disciplines from history, culture, and politics to anthropology.s